Sistem Kendali Material Handling Doors Operation Menggunakan PLC Siemens S7-300 pada Mesin Furnace Area Bar Mill di PT. Krakatau Baja Kontruksi - Fredy Kusuma Nugraha; Mustofa Abi Hamid (Jurnal Sains dan Teknologi, 2024)
Material handling is a form of transportation or conveyance carried out in an industrial company environment. This activity involves moving raw materials, semi-finished goods, or finished goods from the location of origin to a predetermined location. One of the material handling is Doors operation which is located in the furnace machine section which functions as a gate to release a billet that has been heated. In Material Handling, especially in doors operation, an automatic control system using a Programmable Logic Controller is needed. The type of PLC used is the Siemens S7-300 PLC. With the method of observation (observation) in the field of all the equipment that is done and with the literature study can be known material handling control system, especially doors operation. From the results of research on material handling doors operation, it can be seen that this control aims as a gate to release a billet either by remote control or direct control, so that billets that have been heated to a temperature of 1200 degrees can come out effectively and will go to several stands to be printed. All stages in material handling, especially doors operation, can be monitored on the CCTV screen and HMI (Human Machine Interface).